PERANCANGAN PERPUSTAKAAN GEMAR MEMBACA BERBASIS WEBSITE UNTUK DESA MEKARJAYA - Alexander, Onki; Isnaini, Eva Nur; Maranti, Pinta; Bawiling, Hendry; Pryanto, Muhammad Bagus; Dimyati, Muhammad (Politeknik Negeri Banjarmasin, 2021)
In the current era of globalization, the world of information is developing so rapidly because it is supported by increasingly sophisticated technological developments. A library is an important tool that can help teaching and learning activities. At this time, Mekarjaya Village does not have a library to support teaching and learning activities. This study aims to increase the reading interest of the Mekarjaya Village community and to design a website-based library to support teaching and learning activities in the village. In making this digital library, PHP is used as an application program and MySQL as a database server which has been summarized in one XAMPP application. The design of this library information system uses the waterfall method which consists of requirements analysis, design, implementation, testing, maintenance, and results analysis. With the existence of this website-based library information system, the community's interest in reading has increased, especially youths and girls in Mekarjaya Village.